Fundamental solutions of the Stokes system in quaternion analysis - Dinh, Doan Cong; Dinh, Doan Cong (Institute of Mathematics, NAS of Ukraine, 2026)
UDC 532.5 The method of quaternionic analysis in fluid mechanics was developed by several generations of mathematicians with numerous important results. We add a small result in this direction. Thus, we introduce a new reformulation of fundamental solutions of the Stokes system within the framework of quaternion analysis and construct integral representations for its solutions.